Patterns of Fertility Preservation and Pregnancy Outcome After Breast Cancer at a Large Comprehensive Cancer Center - Dieci, Maria Vittoria (J Womens Health (Larchmt), 2019)
Background: In the last decades, long-term outcomes of breast cancer (BC) patients have improved, raising new survivorship issues, including fertility preservation and safety of pregnancy after BC. This study assesses evolution in patterns of fertility discussion/preservation over time and reports pregnancy outcomes in a cohort of young BC patients. Methods: A retrospective cohort of 590 BC patients aged ≤40 diagnosed between 2000 and 2016 at a large cancer center was identified. Fertility counseling and preservation patterns for patients receiving chemotherapy were analyzed and compared for two cohorts: 2004–2006 and 2014–2016 (total n = 161). Outcomes were reported for patients with documented pregnancy after BC. Results: Significantly, more patients diagnosed in 2014–2016 had evidence of discussion on fertility issues and/or application of fertility preservation techniques versus patients diagnosed in 2004–2006 (82.9% vs. 66.0%, p = 0.017). In particular, there was a significant difference in rate of documented fertility issues discussion (67.6% vs. 34.0%, p < 0.001). Age >35 and parity were associated with lower rates of fertility discussion/preservation. However, rates significantly improved over time (77.6% in 2014–2016 vs. 58.1% in 2004–2006 for patients aged >35, p = 0.046; 80.7% in 2014–2016 vs. 57.6% in 2004–2006 for patients with children at diagnosis, p = 0.018). Twenty-six patients with pregnancy after BC were identified; eight delivered at the age of >40. No complications for women or newborns were reported. Only two patients experienced BC relapse. Conclusions: In this small retrospective cohort, no safety concerns were identified for pregnancy after BC. The importance attributed by clinicians to address fertility issues has increased over time.